Aligning Shariah And Environmental, Social, And Governance Criteria In Islamic Finance Perspective - Rodrigo Bochner (SAN Scientific, 2026)
This study addresses a conceptual and practical gap in the literature regarding the systematic alignment between Shariah principles and Environmental, Social, and Governance (ESG) criteria within Islamic finance. Although both frameworks emphasize ethical conduct, social responsibility, and sustainable value creation, existing studies typically examine Shariah compliance and ESG performance in isolation, resulting in fragmented insights and a lack of an integrated analytical framework. This research aims to explain how Shariah principles can be aligned with ESG dimensions particularly governance and social responsibility and to identify challenges that hinder their effective integration into Islamic financial products. Using a qualitative research design, the study employs document and thematic analysis of prior empirical studies, regulatory standards, and institutional reports related to Islamic finance and ESG practices. The findings show that Shariah governance plays a key role in enhancing ESG performance; however, inconsistencies in interpretation, measurement, and regulatory harmonization remain significant obstacles. This study contributes an integrative perspective that positions Shariah as a normative framework capable of strengthening ESG objectives and advancing sustainable Islamic finance.